Biaryl Diketone Synthesis via Palladium‐catalyzed Carbonylative Coupling with Carbon Monoxide or Various Metal Carbonyls. (26th September 2016) - Cho, Soo Kyung; Song, Ju Hyun; Hahn, Jung Tae; Jung, Dai il
Abstract : Biaryl diketones were synthesized via palladium‐catalyzed carbonylative coupling in the presence of a palladium N‐heterocyclic carbene complex and CO or metal carbonyls. Different arylboronic acids along with various CO‐releasing molecules were tested to study the influence of structure. Generally, steric hindrance of arylboronic acids and CO‐releasing ability of various metal carbonyls played significant roles. In most cases, single ketone products were found as the side products rather than direct coupling products. Abstract :